Intrinsic Resistance of Chronic Lymphocytic Leukemia Cells to NK Cell-Mediated Lysis Can Be Overcome In Vitro by Pharmacological Inhibition of Cdc42-Induced Actin Cytoskeleton Remodeling - Wurzer, Hannah; Filali, Liza; Hoffmann, Céline; Krecke, Max; Biolato, Andrea Michela; Mastio, Jérôme; De Wilde, Sigrid; François, Jean Hugues; Largeot, Anne; Berchem, Guy; Paggetti, Jérôme; Moussay, Etienne; et al. (Frontiers in Immunology, 2021)
Natural killer (NK) cells are innate effector lymphocytes with strong antitumor effects against hematologic malignancies such as chronic lymphocytic leukemia (CLL). However, NK cells fail to control CLL progression on the long term. For effective lysis of their targets, NK cells use a specific cell cell interface, known as the immunological synapse (IS), whose assembly and effector function critically rely on dynamic cytoskeletal changes in NK cells. Here we explored the role of CLL cell actin cytoskeleton during NK cell attack. We found that CLL cells can undergo fast actin cytoskeleton remodeling which is characterized by a NK cell contact induced accumulation of actin filaments at the IS. Such polarization of the actin cytoskeleton was strongly associated with resistance against NK cell mediated cytotoxicity and reduced amounts of the cell death inducing molecule granzyme B in target CLL cells. Selective pharmacological targeting of the key actin regulator Cdc42 abrogated the capacity of CLL cells to reorganize their actin cytoskeleton during NK cell attack, increased levels of transferred granzyme B and restored CLL cell susceptibility to NK cell cytotoxicity. This resistance mechanism was confirmed in primary CLL cells from patients. In addition, pharmacological inhibition of actin dynamics in combination with blocking antibodies increased conjugation frequency and improved CLL cell elimination by NK cells. Together our results highlight the critical role of CLL cell actin cytoskeleton in driving resistance against NK cell cytotoxicity and provide new potential therapeutic point of intervention to target CLL immune escape.